2014
DOI: 10.1116/1.4894453
|View full text |Cite
|
Sign up to set email alerts
|

Surface and grain boundary scattering in nanometric Cu thin films: A quantitative analysis including twin boundaries

Abstract: Articles you may be interested inSize effects in thin gold films: Discrimination between electron-surface and electron-grain boundary scattering by measuring the Hall effect at 4K

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 38 publications
3
42
0
Order By: Relevance
“…4,24 With twin boundaries included in the determination of grain size as mean-intercept length, the resistivity data are well described by p and R parameters that are within experimental error equal to those previously reported in Ref. 1. Furthermore, it is shown that exclusion of the twin boundaries results in a worse fit to the experimental resistivity data.…”
Section: Introductionsupporting
confidence: 50%
See 4 more Smart Citations
“…4,24 With twin boundaries included in the determination of grain size as mean-intercept length, the resistivity data are well described by p and R parameters that are within experimental error equal to those previously reported in Ref. 1. Furthermore, it is shown that exclusion of the twin boundaries results in a worse fit to the experimental resistivity data.…”
Section: Introductionsupporting
confidence: 50%
“…1 The values of p and R were varied in steps of 0.01 from 0.01 to 0.99 and the errors, E ¼ q experiment i À q model i , were calculated for each of the experimental resistivity results over the full grid of p and R. The error values for the minimum SSE were used to determine the BIC using Eq. (5).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations